Improvement of preventive inspection and clinical examination in outpatient conditions based on simulation - E. D. Tepluakova; S. M. Shcherbakov (Кубанский научный медицинский вестник)
The introduction of information technology in the work of the medical organizations of various levels is one of the urgent tasks of modernization. Constructed visuals and simulations of processes of medical examination and preventive inspections in the medical organization. The simulation results allow to estimate the costs of doctors, nurses and support staff; select the most labor-intensive processes and operations; to forecast labor in depending on expected number of adult and juvenile patients; find ways to improve the efficiency of the medical organization.